If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) + 2(x + 1) = 5 Reorder the terms: 2(1 + x) + 2(x + 1) = 5 (1 * 2 + x * 2) + 2(x + 1) = 5 (2 + 2x) + 2(x + 1) = 5 Reorder the terms: 2 + 2x + 2(1 + x) = 5 2 + 2x + (1 * 2 + x * 2) = 5 2 + 2x + (2 + 2x) = 5 Reorder the terms: 2 + 2 + 2x + 2x = 5 Combine like terms: 2 + 2 = 4 4 + 2x + 2x = 5 Combine like terms: 2x + 2x = 4x 4 + 4x = 5 Solving 4 + 4x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4x = 5 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = 5 + -4 4x = 5 + -4 Combine like terms: 5 + -4 = 1 4x = 1 Divide each side by '4'. x = 0.25 Simplifying x = 0.25
| 3.3q-3.2-5.1q=0.8q-3.2 | | 6y+9=5y-5 | | x+ax+b= | | 7.1t-8=7.1t-8 | | 3i(7i)= | | 13y+39=11y+15 | | x^2+x(1-6q+q^2)+(-4q^3+8q^2-4q)=0 | | -5(2t-4)+6t=3t-5 | | 12-12x=23x | | y=4-3x+3 | | -4x^4(8-8x+3x^4)=0 | | 3(4z-8)-2= | | 10.50a+82=2017.50 | | 27=-9x-3y | | 14+0.1(x-300)=32.80 | | 3a-3b+3c=0 | | 5a+3b+2c=3a-3b+3c | | -3(4t-2)+5t=4t-4 | | 3a-3b+3b=0 | | z^2-2y+7z^2-2y+6z^2-22z^3+2-16y+2z^3= | | 5a+3b+2c=3a-3b+3b | | 9x-1=9(x-3) | | 5a+3b+2c=3a | | 14-7+12-18= | | 14ab-7ab+12b-18a+bc= | | 7x^4-14x^4+3x^3= | | 86-(3x+16)=3(x+7)+x | | 2(2m-2)-21= | | y=-1.04x+50.3 | | -3(0)+6y=-18 | | -3(5t-5)+7t=2t-6 | | 0=x^2-20x-224 |